Nonlinear FEA of soil-structure-interaction effects on RC shear wall structures - AlHamaydeh, Mohammad; Markou, George; Saadi, Dina (My University, 2017)
Considering Soil-Structure-Interaction (SSI) in Finite Element Analysis (FEA) is accounted for through explicit representation of the soil domain allowing for departures from fixed base conditions and constraints. The performance evaluation of a six-story reinforced concrete (RC) shear wall with and without SSI is presented in this paper. The soil domain and Reinforced Concrete (RC) elements including walls, slabs, and foundations are modeled using 3D 8-noded hexahedral brick elements. Furthermore, longitudinal and transverse reinforcement are modeled as embedded rod elements while the cracking of concrete is modeled via the smeared crack approach. Nonlinear pseudo-static and cyclic pushover analyses are carried out on fixed and flexible base models. The soil in the flexible base model represents a site class E soil type according to ASCE7-10. A parametric study is performed on different pushover loading profiles prior to the comparison between fixed and flexible base systems. The performance evaluation of the two systems is done through direct comparison of pushover curves, displacement, strain locations and cracking patterns. Based on the numerical findings, the RC wall in the SSI model is found to exhibit higher lateral displacements yet lesser levels of strain concentrations for the any given horizontal deformation. Additionally, the superstructure toughness developed in the fixed base model is higher than the SSI model due to the vertical displacement of the soil medium. Finally, cracks in the slabs are found to be more prominent in the SSI model at the upper floors due to the accumulated lateral displacement of the wall and the overall more flexible behavior of the model. In conclusion, soil flexibility (SSI) is found to have a considerable effect on the overall structural system behavior.
Keywords: Nonlinear; FEA; Reinforced Concrete; Soil-Structure-Interaction